2004
DOI: 10.3354/dao058245
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic squamous cell carcinoma in two loggerhead sea turtles Caretta caretta

Abstract: We received 2 stranded loggerhead sea turtles (Caretta caretta) with squamous cell carcinomas to necropsy. The dead turtles had been collected in Gran Canaria and Fuerteventura in April 1994 and May 1997, respectively to determine the cause of death. One turtle had 3 ulcerated lesions in the dorsal part of the neck and several irregular masses in the lungs and kidneys. Histologic examination of lesions in the skin, lungs, kidneys, and ventricular myocardium revealed neoplastic proliferation of abnormal keratin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 13 publications
2
24
0
1
Order By: Relevance
“…Metastatic spread of SCC in reptiles is rare and has been reported in only three cases of turtles. 7,9 Humoral hypercalcemia of malignancy (HHM) is a paraneoplastic syndrome commonly associated with several mammalian tumors but to the authors knowledge it has not been described in reptiles. HHM is caused by de novo secretion of parathyroid hormone-related protein (PTHrP) by the tumor cells or thought to be associated with tumor induced osteolysis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Metastatic spread of SCC in reptiles is rare and has been reported in only three cases of turtles. 7,9 Humoral hypercalcemia of malignancy (HHM) is a paraneoplastic syndrome commonly associated with several mammalian tumors but to the authors knowledge it has not been described in reptiles. HHM is caused by de novo secretion of parathyroid hormone-related protein (PTHrP) by the tumor cells or thought to be associated with tumor induced osteolysis.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Within the order of testudines several cases of SCC have been described in turtles. 2,[7][8][9][10][11] However, in the family testudinidae (tortoises) only two cases of SCC has been reported so far, in a Brazilian giant tortoise (Chelonoidis denticulata, formerly Geochelone denticulata) 12 and in a Hermann's tortoise. 13 The skin is the most common site to develop SCC in chelonians but oral, 6,12 and coelomic 8 SCC can also be present.…”
Section: Introductionmentioning
confidence: 99%
“…Attempts to characterise the tumour immunohistochemically have failed, as no positive colour reaction could be detected. This result can be explained by the fact that cells of reptile origin do not react to antibodies routinely used in the identification process of human cells, as previously reported (Orós et al, 2004). Due to the fact that the slides stained with HE were self-explanatory and the pathological process could be easily identified, the negative results of the IHC investigations did not interfere with the diagnostic process.…”
mentioning
confidence: 52%
“…Its occurrence, in our case, can be explained by the location of the nodule, given that the lump protruded out of the oral cavity, suffering all kinds of friction. Recent studies have found high recurrent and metastatic potential of this neoplasm in snakes and other reptiles (Ramis et al 1998, Orós et al 2004, Hes et al 2007, Orós et al 2009, Salinas et al 2013, Sharpe et al 2013). In our case there was recurrence of fibrosarcoma in about 60 days after surgical removal of the primary nodule.…”
Section: Discussionmentioning
confidence: 96%
“…However, recent studies have found high recurrent and metastatic behavior of this and other neoplasms in snakes and other reptiles (Ramis et al 1998, Orós et al 2004, Hes et al 2007, Orós et al 2009, Salinas et al 2013, Sharpe et al 2013). On clinical examination, the fibrosarcomas are presented as small or large nodular mass and soft to firm consistency, which impair biological functions of some snakes such as swallowing.…”
Section: Introductionmentioning
confidence: 97%